Pengaruh Parental Career-Related Behavior terhadap Kesulitan Pengambilan Keputusan Karir Siswa SMA Kelas 12 di Kota Bandung - Hanifa Khoirunnisa Azahra; Sartika, Dewi; Muhamad Arif Saefudin (Bandung Conference Series: Psychology Science, 2024)
Abstract. The purpose of this study was to determine the effect of parental career-related behavior on career decision-making difficulties. Difficulties in career decision making can be experienced by adolescents before or after decision making, especially high school students are in a critical phase to determine their career choices, so that the role of parents is needed, parental behavior in career development can vary, known as parental career-related behavior (support, interference, lack of engagement). The method used in this study is a quantitative non-experimental approach with a cross-sectional design conducted with 318 12th grade high school students in Bandung City. The sampling method is non probability sampling with convenience sampling technique. The measuring instrument used was the parental career-related-behavior instrument from Dietrich & Kracke (2009). Career decision difficulties questionnaire developed by Gati et al. This study uses multiple linear regression analysis techniques, with the results showing that there is a negative influence of parental career-related behavior support on career decision difficulties, with a large influence of 4.5%. There is a positive influence of parental career-related behavior on career decision-making difficulties with a large influence of 17.9%, there is a positive influence of lack of engagement parental career-related behavior on career decision-making difficulties. Abstrak. Tujuan penelitian ini untuk mengetahui pengaruh parental career-related behavior terhadap kesulitan pengambilan keputusan karir. Kesulitan dalam pengambilan keputusan karir dapat dialami remaja sebelum ataupun sesudah pengambilan keputusan, terlebih lagi siswa SMA berada pada fase kritis untuk menentukan pilihan karirnya, sehingga dibutuhkan peran dari orangtua, perilaku orangtua dalam pengembangan karir dapat beragam yang dikenal dengan parental career related behavior (support, interference, lack of engagement). Metode yang digunakan pada penelitian ini yaitu, pendekatan kuantitatif non eksperimen dengan desain cross-sectional dilakukan dengan subjek penelitian sebanyak 318 siswa SMA kelas 12 di Kota Bandung. Metode pengambilan sampel yaitu, non probability sampling dengan teknik convenience sampling. Alat ukur yang digunakan adalah parental career related-behavior instrument dari Dietrich & Kracke (2009). Career decision difficulties questionnaire yang dikembangkan oleh Gati et al. Penelitian ini menggunakan teknik analisis regresi linier berganda, dengan hasil penelitian menunjukan bahwa terdapat pengaruh negative support parental career-related behavior terhadap kesulitan pengambilan karir, dengan besar pengaruh 4.5%. Terdapat pengaruh positif parental career-related behavior terhadap kesulitan pengambilan keputusan karir dengan besar pengaruh 17.9%, terdapat pengaruh positif lack of engagement parental career-related behavior terhadap kesulitan pengambilan keputusan karir dengan besar pengaruh 24.8%.